Analisis Tingkat Kepuasan Pelanggan untuk Pengembangan Sistem Penyediaan Air Minum: Studi Kasus: SPAM Sukabumi - Herawati Zetha Rahman (Jurnal Infrastruktur, 2024)
Drinking water is one of the basic human needs and is very important to improve the quality of human life and economic growth of the country. In 2020 Sukabumi City with a population of 346,325,000 people, the reliability of clean water is one of the determining indicators of population welfare. With the availability of water, the health and productivity of the community can be maintained, which in turn has a significant economic impact on the community. This study aims to measure the level of public satisfaction with the quality and level of service of drinking water providers in Sukabumi City. The data was collected from primary data, namely area observation and questionnaire distribution, while secondary data was obtained from location maps, document research and supervisory decision 63 A/PDAM/KPTS/2011 on Minimum Service Standard Regulations. The analysis method used is the Critical Performance Analysis (IPA) method which compares the actual score with the expectations of 5 main variables namely; Connection Quality, Payment, Service, quality, quantity, and accuracy of water meters. with a calculated decision limit value of 91.84% and Customer Satisfaction Index (CSI) to achieve SPAM customer satisfaction scores. The results of existing calculations show that Sukabumi customer satisfaction reached 86.87%, which means that they are “very satisfied” with the performance of PERUMDA AIR MINIUM TIRTA BUMI WIBAWA CITY OF SUKABUMI. Thus with the current CSI Index the company may secure the long-term sustainability of its operations